Association of characteristics of HBV quasispecies with hepatitis B surface antigen seroconversion after pegylated interferon-α-2a treatment in child patients. Issue 7 (October 2018) - Yang, Juncheng; Yang, Guifeng; He, Haitang; Ning, Lu; Liu, Zhihua; Fu, Qunfang; Chen, Haitao; Deng, Haohui; Wang, Zhanhui; Luo, Kangxian
Background: The correlation between hepatitis B surface antigen (HBsAg) seroconversion and the characteristics of HBV quasispecies (QS) before and during pegylated interferon-α-2a (PEG-IFN-α-2a) treatment in hepatitis B e antigen (HBeAg)-positive chronic hepatitis B (CHB) children has not yet been reported. Methods: 35 patients, including 18 HBsAg seroconverters (SS) and 17 non-seroconverters (SN), were enrolled. Serum samples were collected before treatment and at weeks 12 and 24 of treatment. Sequences within the basal core promoter/pre-core (BCP/PC) and S/reverse transcriptase (S/RT) region were analysed by next-generation sequencing. Results: There was no significant difference in the baseline diversity of HBV QS (Shannon entropy [Sn]; Hamming distance [HD]) in either region between the two groups. The baseline mutations A1762T/G1764A, C1913A, and T2003A/G or C2004T were correlated with non-response to therapy ( P =0.025, P =0.036, P =0.032, respectively). After 24 weeks of therapy, HBV diversity within the BCP/PC region in the SS group notably declined (Sn: P =0.002; HD: P =0.011), while that of the SN group was nearly unchanged. As for the S/RT region, 24 weeks of treatment made no significant difference on QS diversity in either group. Conclusions: Our data demonstrated that the baseline viral mutations and dynamic changes in HBV QS diversity within the BCP/PC region were closely related to HBsAg seroconversion in HBeAg-positive CHB children treated with PEG-IFN-α-2a.